Changes in protein and amylase in the blood and lymph animals with pancreatitis (Experimental biology, 2016)
Under the acute pancreatitis in rats that was confirmed by histological and biochemical data, the acute experimental pancreatitis showed increased content amylase, lipasa, alkaline phosphate, glucose, ALT, AST, leucocytosis, lymphocytosis, decline of red corpuscles, haemoglobin, general albumen in the lymph and blood. There was found the increase of lymph flow and the rheological properties of disturbance of the lymph and blood, viscidity rose, time of coagulability of lymph and blood shortened, increased number of thrombocytes of blood, that worsened fluidity, both blood and lymph and showed the phenomenon of inflammatory process. Pancreatitis occur in the body pathological changes. Pancreatitis develops as chronic and acute pancreatitis. Scientists are interested to explore the lymphatic system in pancreatitis. Decrease in protein cause acute pancreatitis limfobrazovaniya reduction in animals. By the dehydration leading pancreatitis decrease the amount of circulating blood. An important role in the development of pancreatitis play imunokomponentnyh infringement of functional activity of cells, we refer to them T lymphocytes, helper, etc.
Keywords: Pancreatitis; amylase; blood plasma; lymph; enzyme.